THE EDUCATIONAL VALUE OF "PAJOGE" DANCE IN THE KA'OMBO TRADITIONAL CEREMONY IN SIOMPU DISTRICT, BUTON SELATAN DISTRICT - Nisa Suketri; Jamilah Jamilah; Selfiana Saenal (xxxx, 2023)
The aims of this research are to 1) identify what Educational Values are contained in the Pajoge Dance at the kaâ€™ombo Traditional Ceremony in Siompu District, South Buton Regency. 2) Describe a qualitative reflection of the Educational Values Of Pajoge Dance at the kaâ€™ombo Traditional Ceremony in Siompu District, South Buton Regency. Using content analysis method. The object oh this research is the pajoge dance. Data collection techniques used in this study are observation, interviews, and documentataion. Besed on the result of the research conducted, it was found that 1) the content of education values contained in the pajoge dance, namely a) moral values in the form of responsibility, discipline, honesty, courage, confidence, patience and ethics b) Sosial values in the form of cooperation, mutual cooperation, and c) values Aesthetics in the form og beauty in movement, costumes, property. 2) reflection of the education value of the pajoge dance is reflected in the costume, various movelents, accessories and the approach used in this study in the property approach.Â